Joystick With Haptic Feedback for Vehicle Maneuvering - Gustafsson, Eric; Persson, Jonathan (My University, 2021)
During this work a force feedback joystick with game changing functions for the marine industry has been developed. The developed joystick can single handed be the main steering device for marine vessels during both docking and normal driving. It can handle all needed input (steering, throttle, gear change), and simultaneously give all expected feedback. It will even provide feedback that you did not think was possible from a joystick, like feedback from the engines, drives and surround sensors. During the work, two modular test rigs were designed and manufactured, eleven different solutions for braking, resistance and feedback in the stick was evaluated, seven new functions were implemented and one prototype was manufactured and tested.
Keywords: joystick; haptic feedback; force feedback; vehicle maneuvering